A rede sentinela de notificação de agravos em saúde do trabalhador/SUS segundo a visão de gestores e trabalhadores da regional de saúde. Rondonópolis/MT - Broch, Nelli (2013)
The matter of worker s health has been getting a bigger attention in the field of social discussions, Public Engagement and Public Health, proving the fragility in the area of injuries and work accidents treatment. This study had as general objective identify the difficulties met in the process of effectuation of Rede Sentinela de Notificação de Acidentes e Agravos em Saúde dos Trabalhadores (Sentinel Network for Notification of Accidents and Injuries in the Workers Health), from the view of the managers and workers at SUSRegional de Saúde de Rondonópolis-MT (Health Public System-Regional Health Center of Rondonopolis-MT), in the period 2009-2011. It s a descriptive-explanatory study, which used the documental research and questionnaire to interview managers and workers from SUS (Public Health System), who answered closed and semi -open questions, according to quantitative analysis. The results indicated the following statement: the notifications of injuries and work accidents in SINAN Sistema de Informação de Agravos e Notificações (SINAN=System of information and notification of injuries) are not in conformity with the records of MPS/DATAPREV, CAT, SUB; there is a high level of sub-notification of data in SINAN; there is a lack of training for workers/SUS; there aren t especifically designated professionals to work with the workers health and the Sanitary Code of Municipalities from Health Regional of Rondonópolis doesn t address aspects concerning the workers health. There fore, it can be concluded that the managers don t have the real knowledge of the cases concerning the work accidents, and because of that, they don t realize the importance of actions to reduce problems of sub-notifications of the care provided at Rede Sentinela (Sentinel Network). It was also concluded that even though the workers have received care, they are not registered, situation which suggests a better effectiveness in the notifications.